PENGARUH FAKTOR DANA TERHADAP UPAYA PENINGKATAN KUALITAS PELAYANAN PUBLIK KABUPATEN INDRAGIRI HILIR - administrator admin; Samihah Khalil Halim (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2016)
The quality of public services is influenced by the availability of funds. Today, KabupatenIndragiri Hilir is consisted of 170 villages where most of them are poor villages, despitereceiving variety of funding to administer good public services. The objective of this study isto investigate the influence of the availability of funding on the quality of public services inthe Regency. The methodology used in this study was the official documents. The documentsanalysis covers four types of funding sources which are the central fund, the provincial fund,the district and village fund in the last 5 years (2008-2012). Data were analyzed of theinfluence of the availability of public funds with the quality of public service using regressiontechniques with t test, F test and the coefficient of determination. The availability of funds forthe wellbeing of the people also had an influence on the quality of public services. In order tofurther improve the quality of public service, particularly in the Regency of Indragiri Hilir.